2006
DOI: 10.3168/jds.s0022-0302(06)72441-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Manure Nitrogen Output and Dietary and Animal Factors in Lactating Dairy Cows

Abstract: A large data set derived from total diet digestibility assessments on lactating dairy cows (535 Holstein-Friesian and 29 Norwegian) was used to examine effects of dietary and animal factors on manure (feces and urine) nitrogen (N) output and to develop mitigation strategies and prediction equations for manure N output in lactating dairy cows. Manure N output was positively and significantly related to live weight, milk yield, dietary crude protein (CP) concentration, dry matter intake, and N intake. Reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
4
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 13 publications
11
81
4
5
Order By: Relevance
“…Yan et al (2007) reported that N intake is an accurate predictor of N excretion in growing beef cattle. The current data confirmed previous reports of a linear relationship between N intake and N excretion, for example by Kebreab et al (2001) and Yan et al (2006 and who reported positive linear relationships between N intake and manure N output. One of the objectives of the current study was to develop similarly equations for prediction of N outputs from modern suckler cows.…”
Section: Energy Requirementsupporting
confidence: 93%
“…Yan et al (2007) reported that N intake is an accurate predictor of N excretion in growing beef cattle. The current data confirmed previous reports of a linear relationship between N intake and N excretion, for example by Kebreab et al (2001) and Yan et al (2006 and who reported positive linear relationships between N intake and manure N output. One of the objectives of the current study was to develop similarly equations for prediction of N outputs from modern suckler cows.…”
Section: Energy Requirementsupporting
confidence: 93%
“…Nitrogen utilisation Numerous researchers have reported that increasing NI is accompanied by an increase in FN and UN (Moore et al, 2004;Yan et al, 2006). Previous results obtained by the analysis of a dataset from 25 studies indicated that the slope of the linear relationship between NI and FN or UN varied Salah, Sauvant and Archimède from 0.20 to 0.39 and 0.38 to 0.68, respectively (Castillo et al, 2000;Huhtanen et al, 2008;Weiss et al, 2009;Kebreab et al, 2010).…”
Section: Omdmentioning
confidence: 96%
“…The 2 extant prediction equations for TN (equations 27 and 28) listed in Table 5 performed better when evaluated with the most recent data than with the complete data. Under the complete data evaluation, the model proposed by Yan et al (2006;equation 28) was within 1 g of the prediction error of the proposed models (equations 5 and 6), but the model by Nennich et al (2005;equation 27) was approximately 20 g larger than both equation 28 and the proposed prediction equations for TN excretion from lactating cows (equations 5 and 6). Under evaluation with the most recent data, both equations 27 and 28 performed slightly better than the proposed models, with a prediction error approximately 2 g smaller than that of equations 5 and 6, suggesting they were all equally suited for predicting TN from lactating cows.…”
Section: Model Evaluationmentioning
confidence: 99%
“…In addition, to compare model performance with extant models, the RM-SPE of 3 FN models (Castillo et al, 2000;Huhtanen et al, 2008;Kebreab et al, 2010), 3 UN models (Castillo et al, 2000;Huhtanen et al, 2008;Kebreab et al, 2010), and 2 TN models (Nennich et al, 2005;Yan et al, 2006) was calculated with both the complete data and the most recent data subset. To assess the models' potential for practical application, the TN prediction equations used in the national GHG inventory (EPA, 2014) were evaluated for prediction accuracy with both the complete and most recent data.…”
Section: Model Evaluation and Comparisonmentioning
confidence: 99%